AROMATHERAPY: ACHIEVING ITS BENEFITS AND USES IN MODERN TIMES - Dewi Erna Marisa; Musheer; Asita Elengoe; Santi Wahyuni; Supriyadi (Adisam Publisher, 2024)
Aromatherapy with gamot essential oils can provide a variety of benefits in everyday life. Gammoth essential oil is known for its calming and stimulating properties. It can be used to reduce stress, anxiety, and improve mood. In addition to its psychological benefits, the essential oil of bergamot also has antibacterial and antiviral properties that can boost the immune system and protect against infection. It also has analgesic properties which can relieve pain and inflammation. There are several ways to use the essential oil of gamut in everyday life. It can be applied using an aromatherapy diffuser to create a soothing atmosphere. Gamot essential oils can also be used in massages by mixing with carrier oils to enhance relaxation and relieve tension. Aromatherapy with gamot essential oils can be a valuable addition to your daily self-care and relaxation routine. Always consult a health professional or aromatherapist for personal advice.